レジームシフトの指標としてのウトウ - 山本, 真理子; 綿貫, 豊; Mariko, Yamamoto; Yutaka, Watanuki (2017)
第8回極域科学シンポジウム/個別セッション：[OB] 極域生物圏 12月6日（水）国立極地研究所 3階多目的会議室 The Eighth Symposium on Polar Science/Ordinary sessions: [OB] Polar Biology Wed. 6 Dec./3F Multipurpose Conference Room, National Institute of Polar Research conference object